THE ROLE OF PROFIT-LOSS SHARING IN DEVELOPMENT of MSMEs - Afkar, Taudlikhul; Utomo, Sigit Prihanto; Miradji, Moch Afrizal; Hariawan, Ferry (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study provides an overview of the development of MSMEs from the perceptions of MSMEs, not from the perspective of Islamic financial institutions. The purpose of this study is to show the development model of MSMEs through a profit-loss sharing agreement that is applied to the type of bound investment. It is applied in the mudharabah muqayyadah contract through the principle of profit sharing distribution. The method used in this study is a survey of MSMEs. The results of this study indicate that the development of MSMEs can be carried out with a mudharabah muqayyadah agreement through the principle of profit sharing distribution. To develop MSMEs in order to gain increased revenue, enlarge business scale, and diversify businesses, there needs to be a fair distribution of profit-loss sharing with the principles of revenue sharing, profit sharing, and agreed risk builders despite restrictions in business management such as the type of business determined by the owner of the fund, there are limits in the management of funds, as well as restrictions in running a business or investment, where businesses run must be guided by sharia principles